Fitase em rações para tilápia-do-nilo na fase de crescimento - Bock, Claudio Luiz; Pezzato, Luiz Edivaldo [UNESP]; Cantelmo, Osmar Angelo; Barros, Margarida Maria [UNESP] (FapUNIFESP (SciELO), 2007)
This research was carried out to compare the effect of phytase on performance, in the incorporation and excretion phosphorus in Nile tilápia. Four diets were used: one standard (contol), composed by 3,200 DE kcal ED/kg of ration and 30.0% CP and supplemented with phosphorus (4.0% of dicalcium phosphate), considering the treatment control, and others three, without phosphorus supplementation, with different phytase levels (1,000, 1,500, and 2,000 uf/kg), with four replication, per a period of 82 days. Circular tanks of fiber glass, with constant flow and aeration were used. The results demonstrated that the use of phytase in diets for fish production can reduce the levels of inorganic phosphorus in the diets and minimizing the impacts caused by phosphorus in the production system and in the natural environment and also can improve the productivity, increasing the amount of feed to be supplied and, consequently, facilitating the increase of biomass of fish to be used per production area. © 2007 Sociedade Brasileira de Zootecnia.
Phytase in diets for Nile tilapia in the growth period
Keywords: Excretion; Fish; Growth; Oreochromis niloticus; Phosphorus; Pollution; Tilapia